PENERAPAN MODEL ALTMAN (Z-SCORE) UNTUK MENGUKUR POTENSI FINANCIAL DISTRESS PERUSAHAAN MASKAPAI PENERBANGAN SEBAGAI DAMPAK PANDEMI COVID-19 - Desiana Rachmawati; Adipura Danang Maulana (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The purpose of the study is to measuring potential financial distress in airlines as the impact of the covid-19 pandemic by applying the altman model ( Z Score ). This study is a descriptive quantitative will analyze the potential for financial distress of airlines companies listed on the IDX, the method used in this study is the altman Z-Scroe as a bankcruptcy prediction tool. The data used in this study is secondary data in the form of financial reports and annual reports of PT Garuda Indonesia Tbk (GIAA), PT AirAsia Indonesia Tbk (CMPP), PT Indonesia Transport & Infrastructure Tbk (IATA), and PT Jaya Trishindo Tbk (HELI) period 2020 and 2021 Quarter III. The result of the study can be concluded that based of the results of the calculation of banckruptcy prediction with altman Z score models that has been carried out on each of the airlines sector companies that are the sample, the classification of the bankruptcy predictions shows the results are indications of banckruptcy.